Integration policy in education and immigrant students' patriotic pride in host countries: A cross-national analysis of 24 European countries. Issue 7 (7th June 2021) - Choi, Soobin; Cha, Yun-Kyung
ABSTRACT: This study aims to examine whether there exists a gap in patriotic pride in host countries between immigrant and native students and whether an integration policy in education would work to narrow the gap. This study assumes that immigrant students' patriotic pride in host countries may not only result from immigrant status but also it may be a result of policy efforts to integrate them into society. With this aim, this study analyzed 72, 371 students in grade 8 across 24 European countries based on the two datasets from the Migration Integration Policy Index and the International Civic and Citizenship Study by employing hierarchical linear modelling analyses. In doing so, this study found that there was a gap between immigrant and native students in terms of patriotic pride in host countries. In addition, there was a significantly positive association between integration policies in education and immigrant students' patriotic pride. The findings suggest that immigrant students are likely to take pride in and be more attached to host countries where government institutionalizes well-developed integration policies in education. This study provides insight into the role of integration policies in promoting immigrant students' socio-political integration in host countries.